Advances in Databases and Information Systems 14th East European Conference, ADBIS 2010, Novi Sad, Serbia, September 20-24, 2010. Proceedings - Catania, Barbara; Ivanović, Mirjana; Thalheim, Bernhard (Springer Berlin Heidelberg, 2011)
aThis book constitutes the refereed proceedings of the 14th East European Conference on Advances in Databases and Information Systems, ADBIS 2010, held in Novi Sad, Serbia on September 20-24, 2010. The 36 revised full papers and 14 short papers were carefully selected from 165 submissions. Tolically the papers span a wide spectrum of topics in the database and information systems field, including database theory, advanced DBMS technologies, design methods, data mining and data warehousing, spatio-temporal and graph structured data and database applications.